THE EFFECTIVENESS OF THE OCCUPATIONAL HEALTH AND SAFETY ASSESSMENT SERIES 18001:2007 PT. SURYA BESINDO SAKTI - Subhi, Sudarman; Septiawan, Catur (Journal of Vocational Health Studies, 2020)
Background: OHSAS 18001:2007 is management system of occupational health and safety international standard which includes the structure of the organization, the planning activities, responsibility, procedure, the process and resources to manage K3 .OHSAS have a purpose for protection against the workers from unwanted things arising from work environment, or activity work itself, it have an impact on safety and health workers, and so as not to cause much loss for from accidents work have image bad a company that can lower image company. Purpose: This study aimed to understand the effectiveness of the occupational health and safety assessment series (OHSAS) 18001:2007 in PT. Surya Besindo Sakti. Method: The research used descriptive qualitative research type and design. Test the validity of data using technique triagulation method. Result: PT. Surya Besindo Sakti still meets the minimum requirements of the application of Occupational Health and Safety Assessment Series (OHSAS) 18001: 2007. With findings of minor incompatibilities 6 and 1 OFI (Opportunity For Improvement) findings. Conclusion: The company is expected to continue to commit to run the Occupational Health and Safety Assessment Series (OHSAS) 18001: 2007 for corporate vision and mission to be achieved, objective must be monitored its achievement every month by each department and ensure all procedures used in the company reviewed and implemented consistently.